Interfaces in metal halide perovskites probed by solid-state NMR spectroscopy. Issue 35 (5th July 2021) - Dahlman, Clayton J.; Kubicki, Dominik J.; Reddy, G. N. Manjunatha
Abstract : This review outlines the prospects for a range of solid-state NMR spectroscopy techniques to facilitate structural understanding of complex interfaces in metal halide perovskites and transport layers for optoelectronic applications. Abstract : Metal halide perovskites (MHPs) are promising light harvesting and emitting materials that have enabled solar energy conversion efficiencies of over 25% in solution-processed single-junction cells, and found applications in flexible electronics, detectors and other display technologies. Research on MHPs has achieved significant fundamental and technological advancements over the last decade, in large part due to improvements in characterization approaches to understand these materials. It has become clear that engineering the interfaces between device layers, and within the MHP layer itself, is crucially important to develop stable and efficient optoelectronic devices. Interfaces in MHP-based devices exhibit varying degrees of order, which manifest heterogeneities in compositions, structures and optoelectronic properties. This review assesses the overall prospects for a range of solid-state (ss)NMR spectroscopy techniques to facilitate structure-based understanding of complex interfaces in MHPs and contact layers. The role of ssNMR in elucidating local compositions and structures, intermolecular connectivity, phase transitions, degradation products and molecular passivation at MHP interfaces is discussed. In addition, an overview of different dynamic processes in MHPs probed by ssNMR is provided. Finally, we discuss perspectives on the development of ssNMR spectroscopy for investigating interfaces in MHPs for various optoelectronics.